Long-Term Outcome of Vitrectomy with Suitable Internal Limiting Membrane Peeling and Air Tamponade for Highly Myopic Foveoschisis-Associated Lamellar Macular Hole - Jia-lin Wang; Yan-ling Wang (Journal of Ophthalmology)
Purpose. To investigate the outcome of pars plana vitrectomy (PPV) with suitable internal limiting membrane peeling (ILM) and air tamponade for patients with highly myopic foveoschisis-associated lamellar macular hole (MH). Methods. This retrospective interventional case series included 11 patients with highly myopic foveoschisis-associated lamellar MH who underwent PPV and indocyanine green-aided ILM peeling up to the temporal vascular arcades. Following air tamponade after surgery, all patients were instructed to maintain a face-down position. The patients were followed up for over 1 year and evaluated for MH closure and the best-corrected visual acuity before and after surgery. Results. The mean ± standard deviation values of patient age, axial length, and follow-up duration were 67.82 ± 6.54 years, 29.21 ± 1.95 mm, and 24.27 ± 8.11 months, respectively. After surgery, the lamellar MH closed in all eyes, and 10 eyes showed vision improvement at the 1-month, 3-month, and final follow-up evaluations. One patient showed decreased vision at 2 years after surgery, with patchy chorioretinal atrophy in the macular region. Myopic foveoschisis showed resolution in three eyes and alleviation in eight. Ten patients underwent cataract surgery during PPV. Conclusion. Extension of ILM peeling up to the temporal vascular arcades and air tamponade after PPV may improve the visual function and rate of MH closure for patients with highly myopic foveoschisis-associated lamellar MH.